Investigating the “Health Halo Effect” on South African consumers created by nutrient content claims on breakfast cereal packaging - Bezuidenhout, Shannon (The IIE, 2022)
To set themselves apart from competitors, food manufacturers regularly increase product attractiveness by emphasising positive aspects through claims that generally enhance overall product appeal. Breakfast cereal manufacturers tend to use this marketing approach, where potentially misleading nutrient claims are printed on product packaging. Ultimately, these deceptive nutrient content claims may create a ‘Health Halo Effect’, causing consumers to infer generalised perceptions of overall product healthfulness based on these claims. In the long term, this deception can negatively impact consumer health due to the consumption of cereals that are not as “healthy” as advertised to be. Research findings can raise awareness around the deceptive nature of these claims and grow consumer knowledge in the interpretation of cereal nutritional information. Following a qualitative interpretivist approach, this study aimed to investigate factors contributing to the influence of this ‘Health Halo Effect’ on South African consumers brought about by nutrient content claims on breakfast cereal packaging. The research process involved one-on-one semi-structured interviews with nine participants. The shared characteristics of the population included South Africans who regularly purchased and consumed breakfast cereals. Additionally, the participants were evenly divided between Generation X, Y and Z. Using a thematic analysis approach to analyse the research, three themes were found to address factors that contribute to the influence of the ‘Health Halo Effect’. These include the lack of knowledge when interpreting and reading nutritional content information, nutrient content claims influence consumer decisions when purchasing breakfast cereal, and assumptions about cereal healthfulness are made without sufficient information. An additional theme found that participants possessed a certain level of awareness towards the unhealthy aspects of cereal and the potential deception of content claims. Ultimately, this awareness may minimise the influence of the ‘Health Halo Effect’ on participants.
Keywords: Health; Consumer behaviour; Buying patterns; Labelling